Photosensitization induced by heterophyllaea pustulata in goats: sequential development of skin lesions - Micheloud, Juan Francisco (2021)
Five adult Saanen goats received a single oral dose of Heterophyllaea pustulata containing 42.25 μg/kg rubiadin (anthraquinone). Treated goats, and three adult untreated goats (controls) were exposed to sunlight and sequential ear skin biopsies, collected before treatment, and at 32 h, 3 days, 8 days and 15 days after treatment, were examined. Changes at 32 h after dosing included epidermal spongiosis, single cell death and acantholysis, an increased BAX/BCL-2 protein ratio, and dermal edema. Lesions at day 3 included epidermal and adnexal necrosis, crust formation and acanthosis. Acanthosis, hyperkeratosis, and dermal fibrosis and neovascularization were present at day 15. Pro-apoptotic (BAX)/anti-apoptotic (BCL-2) protein ratio increased at 32 h, whereas epidermal and dermal PCNA immunolabelling increased between days 8 and 15 after treatment. The cutaneous lesions were consistent with sunlight-induced damage and the occurrence in treated but not control goats indicates photosensitization.